From Stiffness to Strength: The Role of Physical Activity in Managing Rheumatoid Arthritis - Mateusz Koper; Kamila Rosińska; Ewelina Justyna Janicka; Agnieszka Perko; Oliwia Bochenek; Julia Natalia Łojewska; Monika Niedźwiedzka; Mateusz Rosiński (Nicolaus Copernicus University in Toruń, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation, pain, and potential disability. While pharmacological treatments are central to managing RA, physical activity plays a crucial role in improving patient outcomes. This article explores the influence of physical activity on RA, detailing its benefits, challenges, and best practices. Physical activity offers numerous benefits for RA patients, including reduced pain, improved joint function, enhanced physical mobility, and better mental health. Regular exercise also mitigates the risk of cardiovascular disease, improves bone density, and contributes to overall quality of life. Suitable forms of physical activity for RA patients include low-impact aerobic exercises, strength training, flexibility exercises, balance training, and mind-body practices like yoga and Tai Chi. Despite these benefits, RA patients face challenges in engaging in physical activity, such as pain, fatigue, and psychological barriers. Properly tailored exercise programs, guided by healthcare professionals, can help overcome these challenges, ensuring that patients can safely incorporate physical activity into their management plans. This article highlights the importance of a multidisciplinary approach, integrating physical activity with conventional RA treatments, to optimize patient outcomes and enhance their quality of life.